Moral knowledge, moral truth and method. Between Aristotle and A. J. Ayer - Bravo, Francisco (Estudios de Filosofía, 2002)
According to some interpreters, the process that A. J Ayer and other analytical philosophers instructed to the cognitive claims of ethics would not have taken place, at least reasonably, if these thinkers had properly understood Nicomachean Ethics VI, 2, 1139 to 21-31 , the only text in which Aristotle defines practical truth. The present communication is an analysis of this fundamental Aristotelian text, from which the existence, not only of a proper moral knowledge, different from the purely theoretical, but also of the truth that corresponds to it, which consists in a conformity not between the dictum and the factum but between the judgment of the practical intellect and the impulse of right desire. There is, then, a lived moral knowledge, which is identified with the deliberation about the means by the end of the action, and a corresponding practical truth, which consists in the conformity between the judgment of the practical intellect, perfected by the phrónêsis, and the correct desire, characteristic of the character perfected by the moral virtues. There is also a moral knowledge thought that, despite the limitations of its object, it is knowledge proper. Aristotle has tried to overcome these limitations through long and assiduous practice of the method.